Occupational Injuries among Dentists in Croatia - Ivana Savić Pavičin; Željka Lovrić; Ayla Zymber Çeshko; Marin Vodanović (University of Zagreb. School of Dental Medicine, 2020)
Objectives: Dental profession is characterized by a high risk of injuries at work due to exposure to specific working conditions. The operating area in a patient's mouth is small, and it is handled by a large number of sharp instruments and drills that rotate at high speed, which creates an aerosol contaminated with particles of saliva and blood. This poses a risk of transmitting infections from patients to the dentist through stabbing incidents and cuts, which are some of the most common occupational injuries that are reported in the scientific literature. Objective: The aim of this study was to examine the frequency of occupational injuries among dentists in Croatia, to establish most common injuries, and to determine the main risk factors. The aim of this research was also to determine the dentists' opinion on causes that are responsible for the occupational diseases and injuries. Material and methods: The survey was conducted based on a sample of 406 dentists from Croatia as respondents to an electronic survey. Results: 63.05% of the respondents suffered injuries caused by dental practitioners. The most common injuries were needle puncture incidents (57.75%) and cuts (20.86%), followed by eye injuries (13.37%), patient bite (4.81%) and punches (1.60%). The largest number of respondents stated the improper posture as the most important cause of occupational diseases and injuries, followed by stress, infection and noise. Conclusion: knowledge of risk factors is the first step of injury prevention. Our respondents were largely aware of the dangers surrounding them. Nevertheless, the frequency of injuries was high and there is still a need for preventive measures to minimize the frequency of injuries in dentistry.